2014
DOI: 10.1002/2014gl060308
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration efficiency in the iron‐limited North Atlantic: Implications for iron supply mode to fertilized blooms

Abstract: Estimates of the amount of carbon sequestered in the ocean interior per unit iron (Fe) supplied, as quantified by the sequestration efficiency (C effx ), vary widely. Such variability in C effx has frequently been attributed to estimate uncertainty rather than intrinsic variability. Here we derive new estimates of C effx for the subpolar North Atlantic, where Fe stressed conditions have recently been demonstrated. Derived values of C effx from across the region, including areas subject to atypical external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
(144 reference statements)
0
20
0
Order By: Relevance
“…Often poor temporal and spatial satellite coverage during an expected response period may simply be preventing detection, yet there are multiple factors responsible for regulating the phytoplankton standing crop that should be anticipated to potentially result in the absence of biomass increase subsequent to a nutrient enrichment event (Cullen et al, 1992;. Continuous low-level input of ash through small, regular eruptions likely fertilizes phytoplankton to some extent, potentially with greater efficiency (Baker and Croot, 2010;Le Moigne et al, 2014), although responses to these can be difficult to identify using remote sensing. New algorithms relating subtle changes in chlorophyll-a biomass (e.g., over baseline averages) to potential nutrient supply could offer a means to better resolve these (O'Malley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often poor temporal and spatial satellite coverage during an expected response period may simply be preventing detection, yet there are multiple factors responsible for regulating the phytoplankton standing crop that should be anticipated to potentially result in the absence of biomass increase subsequent to a nutrient enrichment event (Cullen et al, 1992;. Continuous low-level input of ash through small, regular eruptions likely fertilizes phytoplankton to some extent, potentially with greater efficiency (Baker and Croot, 2010;Le Moigne et al, 2014), although responses to these can be difficult to identify using remote sensing. New algorithms relating subtle changes in chlorophyll-a biomass (e.g., over baseline averages) to potential nutrient supply could offer a means to better resolve these (O'Malley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to total fluxes, differences in modes of delivery could be particularly important for Southern Ocean biogeochemistry. Volcanic deposition is dominated by transient pulses whereas dust supply is somewhat more continuous; the former likely leading to both reduced Fe release and carbon export efficiencies than continuous low-level supply (Baker and Croot, 2010;Le Moigne et al, 2014). Thus, on thousands of year timescales, ash-fertilized carbon export from Patagonian volcanism is likely orders of magnitude lower than dust, whilst individual eruptions could likely feature significantly at the interannual scale.…”
Section: Carbon Sequestration Potential Of Volcanic Ash Deposition Evmentioning
confidence: 99%
“…[]. Cruise D354 was undertaken in July–August 2010 in the Irminger Basin (IrB) and Iceland Basin (IB) in the high‐latitude NA [ Le Moigne et al ., ]. Cruise JC071 took place within 30 km of the PAP site, between 29 April and 12 May 2012 and covered the start of the phytoplankton spring bloom.…”
Section: Methodsmentioning
confidence: 99%
“…While numerous artificial (Boyd et al, 2000(Boyd et al, , 2004Gervais et al, 2002;Buesseler et al, 2004Buesseler et al, , 2005de Baar et al, 2005;Hoffmann et al, 2006;Boyd et al, 2012;Smetacek et al, 2012) and natural (Blain et al, 2007;Pollard et al, 2009;Zhou et al, 2010Zhou et al, , 2013 ocean iron-fertilization experiments in the Southern Ocean have demonstrated the role of iron in enhancing the phytoplankton biomass and production in high-nutrient low-chlorophyll (HNLC) regions, determining to what extent fertilization could modify the transfer of particulate organic carbon (POC) to the deep ocean is far from being comprehensively achieved (Lampitt et al, 2008;Morris and Charette, 2013;Le Moigne et al, 2014;Robinson et al, 2014). This is partly due to the short term over which the observations were made, precluding extrapolation to longer timescales.…”
Section: Introductionmentioning
confidence: 99%